A patient-centric dataset of images and metadata for identifying melanomas using clinical context - Veronica Rotemberg (Nature Portfolio, 2021)
Measurement(s) melanoma • Skin Lesion Technology Type(s) Dermoscopy • digital curation Factor Type(s) approximate age • sex • anatomic site Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13070345